Global competitiveness and corruption: A panel analysis in Asean countries - Kok, Hui Ying (2022)
This paper attempts to assess the determinants that affect the GCI in ASEAN countries. It is known that the GCI allows decision-makers to evaluate the productivity of individual sectors and the economy as a whole for each country. Besides, it has nine pillars that are classified into three sub-indices, where a total of ninety variables are composed to determine a country's competitiveness. Hence, it is beneficial to examine the set of institutions, policies, and variables that govern the degree of economic success that can be sustained in both the short-run and long-run. Furthermore, the World Economic Forum (WEF) has compiled a Global Competitiveness Index (GCI) as a study on the competitiveness of countries around the world, including ASEAN countries since 2004. This study focuses on the ASEAN nations that make up the AEC's axis. This community is committed to boosting ASEAN's capabilities to pursue the flow of barrier-free liberalization and trade while also enhancing the international trade system's legislation and regulations. Consequently, the ASEAN countries' competitiveness index should always be evaluated. The study is only undertaken in ASEAN-7 nations, including Cambodia, Indonesia, Malaysia, Philippines, Singapore, Thailand, and Vietnam, due to data limitations in various countries. In our research, the Ordinary Least Squares (OLS) method is employed to explore the relationship between the explanatory variables (Control of Corruption (CCI), Gross Domestic Product (GDP), FDI inflows, Trade Openness, Gross Fixed Capital Formation (GFCF)) and the dependent variable (global competitiveness index). Lastly, the empirical findings indicate that the CCI, GDP, and FDI have an impact on ASEAN countries’ GCI. The CCI, GDP, and FDI are proven to have a positively favorable link with GCI in ASEAN countries. On the other hand, the moderating effect between CCI and GDP with CCI and FDI has a negative influence on GCI. However, the remaining control variables, namely trade openness and GFCF, were shown to have little or no effect on GCI among the ASEAN nations.